2022
DOI: 10.1200/jco.2022.40.16_suppl.4518
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results of a phase Ib/II combination study of RC48-ADC, a novel humanized anti-HER2 antibody-drug conjugate (ADC) with toripalimab, a humanized IgG4 mAb against programmed death-1 (PD-1) in patients with locally advanced or metastatic urothelial carcinoma.

Abstract: 4518 Background: RC48-ADC has shown promising data in HER2-positive and even negative patients with metastatic urothelial carcinoma (mUC) who failed with platinum-based chemotherapy. RC48-ADC combined with anti-PD-1 antibody may have a synergistic antitumor effect. Methods: This is an open-label, multicenter, phase 1b/II trial to evaluate the safety and activity of RC48 combined with toripalimab in mUC. Patients received RC48-ADC at 1.5 or 2 mg/kg, in combination with 3mg/kg toripalimab every two weeks in a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…27 Moreover, the median PFS (6.9 months) was numerically superior to the outcomes of the combined analysis of the RC48-C005 and RC48-C009 studies (5.9 months), the outcomes of the RC48-C011 study (5.5 months), 16 and the data of Chen et al (5.4 months). 27 The study also included 30 patients who received RC48 in combination with a PD-1 inhibitor, showing an ORR of 66.7%, lower than the RC48-C014 study result (76.7%), 19 but higher than that reported by Chen et al (38.8%). 27 The median PFS of 8.2 months was lower than the RC48-C014 study result (9.2 months) but similar to the real-world data from Chen et al (8.5 months).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…27 Moreover, the median PFS (6.9 months) was numerically superior to the outcomes of the combined analysis of the RC48-C005 and RC48-C009 studies (5.9 months), the outcomes of the RC48-C011 study (5.5 months), 16 and the data of Chen et al (5.4 months). 27 The study also included 30 patients who received RC48 in combination with a PD-1 inhibitor, showing an ORR of 66.7%, lower than the RC48-C014 study result (76.7%), 19 but higher than that reported by Chen et al (38.8%). 27 The median PFS of 8.2 months was lower than the RC48-C014 study result (9.2 months) but similar to the real-world data from Chen et al (8.5 months).…”
Section: Discussionmentioning
confidence: 84%
“…Recently conducted Phase II multicenter randomized controlled studies, namely RC48‐C005, RC48‐C009, and RC48‐C011, demonstrated robust ORR and PFS data for UC treated with RC48‐ADC monotherapy, regardless of HER2 expression (IHC 3+, 2+, 1+, or 0), after progression on standard chemotherapy 16–18 . The latest RC48‐C014 study confirmed that the combination of RC48‐ADC with the programmed cell death protein 1 (PD‐1) inhibitor toripalimab outperformed RC48‐ADC monotherapy in terms of ORR and median PFS 19 …”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…The most often used immunotherapeutic agents in combination with ADCs appears to be confined to PD-1 inhibitors with pembrolizumab , and nivolumab dominating and followed by atezolizumab, , durvalumab and toripalimab and are currently in various stages of clinical trials. A few representative examples of patents for ADC immunotherapy combination therapy are WO2018160538, US20220133902, WO2022242692, WO2018110515 .…”
Section: Adc-based Combination Therapiesmentioning
confidence: 99%